2021
DOI: 10.1103/physrevb.103.245410
|View full text |Cite
|
Sign up to set email alerts
|

Strong in-plane anisotropy in the electronic properties of doped transition metal dichalcogenides exhibited in W1xNbxS2

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The clustering feature was previously observed for Nb (7% or 10%)-doped WS 2 and Nb (12.8%)-doped WSe 2 , which were synthesized using CVD (at 550 or 1000 °C) and CVT (at 1000 °C), respectively. 13,21,22 The Mo 0.5 W 0.5 S 2 (synthesized using CVD at 800 °C) and Re 0.5 Nb 0.5 S 2 (synthesized using CVT at 930− 960 °C) crystals also showed the stripe-type atomic ordering. 41,42 Therefore, it is no striking issue to observe the separated domains for the present W 1−x Nb x Se 2 nanosheets synthesized at the lower temperatures.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The clustering feature was previously observed for Nb (7% or 10%)-doped WS 2 and Nb (12.8%)-doped WSe 2 , which were synthesized using CVD (at 550 or 1000 °C) and CVT (at 1000 °C), respectively. 13,21,22 The Mo 0.5 W 0.5 S 2 (synthesized using CVD at 800 °C) and Re 0.5 Nb 0.5 S 2 (synthesized using CVT at 930− 960 °C) crystals also showed the stripe-type atomic ordering. 41,42 Therefore, it is no striking issue to observe the separated domains for the present W 1−x Nb x Se 2 nanosheets synthesized at the lower temperatures.…”
Section: Resultsmentioning
confidence: 98%
“…19,20 Scanning transmission electron microscopy (STEM) images revealed the anisotropic atomic distribution with clusters or stripes of Nb (∼10%) doped in WS 2 or WSe 2 . 13,21,22 Salehi-Khojin's group predicted theoretically the homogeneous single phase of the W 1−x Nb x Se 2 alloy at 780 K and synthesized it at 1300 K. 23 Researchers have synthesized composition-tuned W 1−x Nb x Se 2 crystals using chemical vapor transport or monolayer films using CVD at 850 °C. 24,25 The direct observation of the W 1−x Nb x Se 2 structure at the atomic scale is essential to understanding their properties, but there has been no reported analysis over a wide composition range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DE F of different alloys as a function of electronegativity of C atom were shown in Fig. 4, where DE F is defined as the difference of formation energy between Ti 1Àx C x B 2 alloys with clustered substitute distribution and isolated substitute distribution [47]. Note that in the clustered substitute distribution, the substituted C atoms were placed at the nearest distances among all A-site positions.…”
Section: Substitute Distribution Of Metal Alloymentioning
confidence: 99%
“…In practice, real ternary material often exhibits a more complex structure in which chemical fluctuations are spatially correlated. Several studies concerning TMDs alloys [71][72][73] have demonstrated that fluctuations along the growth direction can lead to ordered configurations in the form of atomic chains oriented parallel to the flake edges (i.e. zigzag directions), akin to ordering observed in the epitaxy of 3D bulk crystals [74].…”
Section: + -mentioning
confidence: 99%